The Influence of Public Information Disclosure and the Use of Social Media by the Probolinggo City Government on Public Trust in Probolinggo City - Fitria, Nurul Jannah Lailatul; Aprilyandi, Ferdy (CV. Austronesia Akademika, 2025)
Good governance emphasizes transparency and accountability, which are increasingly facilitated through digital media, particularly social media platforms that provide rapid, interactive, and borderless communication. In Indonesia, Law Number 14 of 2008 on Public Information Disclosure mandates openness as a democratic right, yet challenges remain in ensuring accessibility, accuracy, and the prevention of misinformation. Against this background, this study aims to examine the influence of public information disclosure and the use of social media by the Probolinggo City Government on public trust. Using a descriptive quantitative approach, data were collected through questionnaires, observation, and documentation involving 100 respondents who actively follow and engage with the official Instagram account @probolinggoimpressive. Data analysis employed Partial Least Squares (PLS) to test convergent validity, discriminant validity, reliability, and structural model relationships. The findings indicate that both information transparency and social media utilization significantly influence public trust, with information transparency contributing 40.8% and social media utilization contributing 39.1% to variations in trust. Hypothesis testing confirmed that the effects of both independent variables on public trust are statistically significant (p < 0.05). The study concludes that consistent and transparent information delivery, coupled with active use of social media, strengthens government credibility and enhances public trust. These results provide practical implications for local governments to adopt more modern, flexible, and two-way communication strategies while addressing the risks of misinformation.